Myositis : Rare Presentation of Dengue, not Uncommon in Children - Parvin, Rukhsana; Saad, Tania; Rouf, Md Abdur (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Dengue myositis is a recently recognized category of idiopathic inflammatory myopathies manifested as symmetric proximal muscle weakness with severe limb pain and high serum creatine kinase (CK) levels, in dengue patient (NS1 positive or IgM positive). A total 4 cases of dengue myositis were admitted at Shaheed Suhrawardy Medical College during the period from August to October, 2023. All were male & they presented mainly with severe limp pain with inability to walk they were diagnosed as dengue fever serologically. Two cases presented during febrile phase & two following fever. Their S. CPK level were high with mildly low platelet count. None of them developed shock or hemorrhagic manifestation. They were treated supportively and all 4 cases recovered without any sequelae. Dengue myositis in children is usually benign and is differentiated from other causes of flaccid paralysis by tenderness of calf and thigh muscles and raised CPK levels with other normal neurological findings. But sometimes it may result in serious consequences, so all children with dengue infection should be followed up carefully with S.CPK level J Bangladesh Coll Phys Surg 2023; 41: 101-104